Chewing the Way to Better Dental Health : A Structured Literature Review on the Impacts of Hard Food on Malocclusion - Kachouh, Farouk; Abbas, Al-Hassan; Kabir, Bilaal; Hafizi, Sayed (Université d'Ottawa | University of Ottawa, 2017)
Background: At present, over 20% of the world’s population have dental malocclusions. Malocclusion is defined as the misalignment of teeth in the dental arches, which leads to an incorrect bite upon closing of the jaw. There are many consequences associated with malocclusions including increased tooth strain, increased risk of cavity formation and chewing complications. Additionally, malocclusions negatively affect quality of life by reducing self-esteem and increasing self-consciousness. Treatment for malocclusion is quite expensive in Canada and typically costs between $3000 and $8000. While genetics may be largely responsible for the development of dental arches and therefore, malocclusions, there is speculation that soft food may be partially responsible. Soft foods are characterized as having soft textures, being easily digestible, and well tolerated. Soft foods are highly abundant in modern and industrialized diets. They provide nutrients in the form of liquids or semisolid foods and include refined dairy, poultry, fruits, vegetables, and grain products. Hard foods, on the other hand, include certain fruits, vegetables, coarse breads, cereals, raw meats, and nuts. These foods are unprocessed or minimally so. Objective: To determine if a diet of hard foods lead to decreased incidence of malocclusion. Method: Conduct a structured literature review of relevant English and French peer-reviewed articles using the databases Scopus and Medline (Ovid). Articles will be analyzed and the population, method, study design, results and target will be outlined. Results: 12 articles pertaining to malocclusion and food consistency were obtained. Human, animal, and evolutionary studies comprise the majority of articles on this topic. Conclusion: Hard foods have been observed to lead to decreased incidence of dental malocclusion when compared to soft foods. Nonetheless, more research needs to be conducted in this area in order to provide a clearer correlation between soft food diets and dental malocclusions.